Transcriptional regulations of pollen tube reception are associated with the fertility of the ginger species Zingiber zerumbet and Zingiber corallinum - Liang, Shan; Hu, Ming-li; Lin, Hao-chuan; He, Han-jun; Ning, Xi-ping; Peng, Pei-pei; Lu, Guo-hui; Sun, Shu-lan; Wang, Xiao-jing; Wang, Ying-qiang; Wu, Hong (Frontiers in Plant Science, 2023)
Zingiber zerumbet and Zingiber corallinum are economically valuable species in the genus Zingiber. While Z. corallinum is sexually active, the Z. zerumbet adopts clonally propagation although it is potential on sexual reproduction. It is unclear so far at which step during the sexual reproduction of Z. zerumbet is blocked, and what are the regulation mechanisms underlying this inhibition. Here, by comparing with the fertile species Z. corallinum using microscopy-based methods, we show that rare differences were observed in Z. zerumbet up to the point when the pollen tubes invaded the ovules. However, a significantly higher percentage of ovules still contained intact pollen tubes at 24 hours after pollination, suggesting pollen tube rupture was impaired in this species. Further RNA-seq analysis generated accordant results, showing that the transcription of ANX and FER, as well as genes for the partners in the same complexes (e.g. BUPS and LRE respectively) and those putative peptide signals (e.g. RALF34), were timely activated in Z. corallinum, which ensure the pollen tubes being able to grow, reorient to ovules and receipt by embryo sacs. In Z. zerumbet, genes for these complexes were cooperatively suppressed, which would result in the maintenance of PT integrity due to the disruption of RALF34-ANX/BUPS signaling in PT and the failure of PT reception by active synergid due to the insufficiency of the synergid-harbored FER/LRE complex. Taken the results from cytological and RNA-seq study together, a model is proposed to illustrate the possible regulation mechanisms in Z. zerumbet and Z. corallinum, in which the regulations for the pollen tube rupture and reception was proposed as the barrier for the sexual reproduction in Z. zerumbet.